Drug reactions with skin manifestations. How to discover? - Yu. G. Haliulin; D. Sh. Macharadze (Лечащий Врач, 2021)
Reasons of appearance and clinical manifestations of toxicodermia were considered. It was indicated that drug reactions with skin manifestations are extremely versatile. In some cases, the doctor cannot cancel the drug, and then the doctor should prescribe the treatment in order to mitigate the side effects of the drug, or find a substitute for this preparation. Regression in the eruptions after the preparation is cancelled also helps find the reason of the disease.